Hubungan Pengetahuan Ibu Dalam Memberikan MP-ASI dengan Kejadian Diare pada Balita Usia 6-24 Bulan di Puskesmas Iwoimendaa - Dasmia, Dasmia; Saehu, Muh. Syaiful; Romantika, I Wayan (Jurnal Gizi Ilmiah, 2023)
Diarrhea is a crucial child problem in the world, which is the cause of around 8% of all deaths of children under 5 years. Many factors are thought to be the cause of diarrhea, one of which is the provision of inappropriate complementary foods. Related to this, mother's knowledge is an important factor in the process of giving complementary breastfeeding. The purpose of this study was to determine the relationship between mother's knowledge in giving complementary breastfeeding and the incidence of diarrhea in toddlers aged 6-24 months at the Iwoimendaa Health Center. This study used a cross-sectional study design with a total sample of 30 mothers of toddlers aged 6-24 months. The research data were analyzed using the fisher's exact test. The research results show that the p-value = 0.467 > α means that there is no relationship between the mother's knowledge in giving complementary breastfeeding and the incidence of diarrhea in toddlers aged 6-24 months at the Iwoimendaa primary health care.